2020
DOI: 10.1007/s11606-020-05951-7
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Screening with Low-Dose CT: a Meta-Analysis

Abstract: BACKGROUND: Randomized controlled trials have evaluated the efficacy of low-dose CT (LDCT) lung cancer screening on lung cancer (LC) outcomes. OBJECTIVE: Meta-analyze LDCT lung cancer screening trials. METHODS:We identified studies by searching PubMed, Google Scholar, the Cochrane Registry, ClinicalTrials.gov, and reference lists from retrieved publications. We abstracted data on study design features, stage I LC diagnoses, LC and overall mortality, false positive results, harm from invasive diagnostic procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 72 publications
(56 reference statements)
2
50
0
4
Order By: Relevance
“…Based on a systematic literature review, we performed a meta-analysis of eight RCTs on LDCT lung cancer screening, including the latest results from European trials published in 2020, comprising a total of more than 87,000 participants. The estimated relative reduction of lung cancer mortality by screening with LDCT was 20% when compared to no screening and 12% across all considered studies, which confirms earlier studies [70][71][72][73]. Although the meta-analysis of included studies did not provide proof of a benefit in all-cause mortality, the effect estimates of most individual studies tend in the same direction as for the lungcancer-specific mortality and indicate a protective effect.…”
Section: Discussionsupporting
confidence: 79%
“…Based on a systematic literature review, we performed a meta-analysis of eight RCTs on LDCT lung cancer screening, including the latest results from European trials published in 2020, comprising a total of more than 87,000 participants. The estimated relative reduction of lung cancer mortality by screening with LDCT was 20% when compared to no screening and 12% across all considered studies, which confirms earlier studies [70][71][72][73]. Although the meta-analysis of included studies did not provide proof of a benefit in all-cause mortality, the effect estimates of most individual studies tend in the same direction as for the lungcancer-specific mortality and indicate a protective effect.…”
Section: Discussionsupporting
confidence: 79%
“…Despite the clear survival benefit of LDCT screening in appropriate patients, there has been a relatively low adherence to these guidelines in clinical practice (8)(9)(10). In addition, several studies have described disparities in the use of LDCT screening in underserved populations, including racial/ethnic minorities (11,12), those living in rural areas with more limited access to care (13), and other vulnerable populations (14,15).…”
Section: Review Articlementioning
confidence: 99%
“…The false positive rate is calculated by dividing the number of false positives by the number of individuals screened with LDCT. Reported false positive rates vary among studies in the literature, ranging from 0.6% to 96% among systematic reviews and meta-analyses (7)(8)(9)(10)13,14). This variability is largely due to differences in the definition of a positive exam.…”
Section: False Positives Examsmentioning
confidence: 99%
“…The rate of estimated ranges from 0-67% in the literature (9,(13)(14)(15). Usman Ali et al (9) reported an overdiagnosis rate of 10.99-25.83% depending on the thresholds used to determine overdiagnosis across studies (44,75,77,78): lead time 5.5 years with mean sojourn time 2 years, lead time ≥5 years, tumor size 30 mm, and tumor volume doubling time ≥400 days.…”
Section: Overdiagnosismentioning
confidence: 99%